Law and religion in a secular age - Domingo, Rafael (The Catholic University of America Press, 2023)
"Essays discussing the relationship of national, international, and canon law to spirituality, God, and religion. The second half of the book discusses the lives of Christians who have made significant contributions to jurisprudence in various spheres: Alberico Gentili, Robert Schuman, Óscar Romero, Pope John Paul II, Álvaro d'Ors, and John Witte, Jr"--